Securitization of Migration and Human Rights: Frictions at the Southern EU Borders and Beyond - Gabrielli, Lorenzo (Lidé města, 2014)
The migratory question in Europe is increasingly viewed from a security-based approach. After analyzing the genesis of this process of securitization of the migration issue, this paper will examine how this securitization of the migration issue shapes the political debate as well as the political answer to immigration. The increasingly strong link between security and migration produces relevant consequences on the Euro-African border: a progressive militarization of the external border as well as a displacement of the latter towards the African continent. At the southern borders of the EU, the external dimension of European immigration policies focuses on the delegation of migration control towards transit spaces in the African continent, creating a number of “buffer-zones” in the continent and displacing the Euro-African border farther south. Using an approach inspired by “migration system analysis,” this paper carries out an analysis of the interactions between migration flows and the external dimension of European immigration policies in the African transit area in order to understand the threats to an effective application of human rights and of the right of asylum. The Euro-African collaboration in migration control, developed during the last decade through different initiatives, underlines the structurally ephemeral character of the short-term securitarian approach of immigration policies. Regardless of the incapability of such policies to stop the departures from the African continent, this reactive process of inter-regional migratory governance building generates significant “side-effects” vis-à-vis human security of migrants and asylum seekers as well as the respect of their rights.